Subanesthetic dose of S-ketamine improved cognitive dysfunction via the inhibition of hippocampal astrocytosis in a mouse model of post-stroke chronic stress. (February 2023) - Zhang, Li-Min; Wu, Zhi-You; Liu, Ji-Zhen; Li, Yan; Lv, Jin-Meng; Wang, Lu-Ying; Shan, Yu-Dong; Song, Rong-Xin; Miao, Hui-Tao; Zhang, Wei; Zhang, Dong-Xue
Abstract: Post-stroke chronic stress (PSCS) is generally associated with the poorer recovery and more pronounced cognitive dysfunction. Recent evidence has implied that S-ketamine can reduce suicidal ideation in treatment-resistant depression. In this current study, we aimed to investigate whether the administration of S-ketamine ameliorated cognitive deficits under PSCS conditions, which was established by a model combining middle cerebral artery occlusion (MCAO) and chronic restraint stress. Our data suggested that mice exposed to PSCS exhibited depression-like behavior and cognitive impairment, which coincided with astrocytosis as indicated by increased GFAP-positive cells and impairment of long-time potentiation (LTP) in the hippocampal CA1. Subanesthetic doses (10 mg/kg) of S-ketamine have significantly mitigated depression-like behaviors, cognitive deficits and LTP impairment, reduced astrocytosis, excessive GABA, and inflammatory factors, including NLRP3 and IL-18 in astrocytes in the CA1. Besides, neuroprotective effects induced by S-ketamine administration were found in vitro but could be partially reversed by an agonist of the NLRP3 nigericin. Our current data also suggests that the subanesthetic doses of S-ketamine improved cognitive dysfunction via the inhibition of hippocampal astrocytosis in a mouse model of PSCS.